Potential Role of Traditional Chinese Medicines by Wnt/β-Catenin Pathway Compared With Targeted Small Molecules in Colorectal Cancer Therapy - Chang, Jinrong; Xavier, Hoileong Wong; Chen, Dongfeng; Liu, Yamei; Li, Hui; Bian, Zhaoxiang (Frontiers in Pharmacology, 2021)
Colorectal cancer (CRC) has become a global public health problem because of its high incidence and mortality rate worldwide. The previous clinical treatment for CRC mainly involves conventional surgery, chemotherapy and radiotherapy. With the development of tumor molecular targeted therapy, small molecule inhibitors present a great advantage in improving the survival of patients with advanced CRC. However, various side effects and drug resistance induced by chemotherapy are still the major obstacles to improve the clinical benefit. Thus, it is crucial to find new and alternative drugs for CRC treatment. Traditional Chinese medicines (TCMs) have been proved to have low toxicity and multi-target characteristics. In the last few decades, an increasing number of studies have demonstrated that TCMs exhibit strong anticancer effects in both experimental and clinical models and may serve as alternative chemotherapy agents for CRC treatment. Notably, Wnt/β-catenin signaling pathway plays a vital role in the initiation and progression of CRC by modulating the stability of β-catenin in the cytoplasm. Targeting Wnt/β-catenin pathway is a novel direction for developing therapies for CRC. In this review, we outlined the anti-tumor effects of small molecular inhibitors on CRC through Wnt/β-catenin pathway. More importantly, we focused on the potential role of TCMs against tumors by targeting Wnt/β-catenin signaling at different stages of CRC, including precancerous lesions, early stage of CRC and advanced CRC. Furthermore, we also discussed perspectives to develop potential new drugs from TCMs via Wnt/β-catenin pathway for the treatment of CRC.